Delineating the lipidated Atg8 structure for unveiling its hidden activity in autophagy. Issue 10 (3rd October 2021) - Maruyama, Tatsuro; Noda, Nobuo N.
ABSTRACT: Atg8 has attracted attention as a central factor in autophagosome biogenesis for a long time. However, the molecular activities of Atg8 on the phagophore membranes as the physiologically functional lipidated form remain enigmatic. In our recent study, we unveiled the hidden physicochemical activity of lipidated Atg8 toward the membrane. Structural analysis revealed that lipidated Atg8 adopts a preferred orientation on the membrane, contacting the membrane using aromatic residues and at the same time exposing cargo binding pockets to the solvent, enabling this small protein to perturb and transform membranes while recognizing autophagic cargos. The membrane perturbation activity was shown to be essential for efficient autophagosome biogenesis, yet questions on the mechanistic roles of Atg8 remain open.